Adenoid Cystic Carcinoma of Breast: A Common Tumour at An Uncommon Site - A Case Report and Literature Review - Walia, Gurpreet Kaur; Yadav, Poonam; Dogra, Natasha; Dwivedi, Surjeet; Akal, Ramanjit Singh (Annals of Pathology and Laboratory Medicine, 2023)
Adenoid Cystic Carcinoma is an uncommon malignancy of breast with favourable prognosis and distinct histomorphology. We present a case of 47 year old female with palpable lump in right breast. Mammogram revealed an irregular hypoechoic solid mass at 10 ‘O clock position with indistinct margins. Trucut biopsy sections revealed a tumour showing pseudoglandular and true gland-like spaces lined by epithelial and myoepithelial cells and filled with abundant homogenous eosinophilic material. Immunohistochemistry revealed triple negative tumour cells, low Ki 67 (1-2 %) with p63 positive in myoepithelial cells and CD117 positive in epithelial cells. With these findings, it was opined as Adenoid cystic carcinoma right breast and the patient underwent wide local excision which we received for histopathological examination. On serial slicing, a solid circumscribed tumour measuring 1x1x2 cm was seen. Sections revealed concurrent morphological and IHC findings as seen on trucut biopsy. Patient responded well to surgery followed by radiotherapy.